MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS MENGGUNAKAN APLIKASI PRACTICE ENGLISH SPEAKING TALK BAGI SISWA KELAS IX-A SMP NEGERI 15 TASIKMALAYA - Rahmat, Ade (LPPM Universitas Bina Bangsa, 2023)
This research was conducted at SMP Negeri 15 Tasikmalaya in Class IX-A where the students' ability to speak English was quite low. The era of digitalization, which is called the era of the industrial revolution 4.0, made very fast changes. Many digital learning applications can be used effectively and efficiently as learning support media. This research requires innovative learning media so students don't feel bored during the teaching and learning process. There are many digital learning applications that can be used effectively and efficiently as learning support media. This classroom action research is entitled: